Analgesic E?ect of Intra Peritoneal and Port Site Instillation of Bupivacaine in Post Laparoscopic Cholecystectomy - Ahuja, Rakshit; Swati Dattaprasad Inamdar; Mrunal Nitin Ketkar (Asian Journal of Medical Research, 2022)
Background: Pain in cases of laparoscopy is a distressing side effect mainly in initial post-operative period. This randomized control study is done to evaluate the local effect of Bupivacaine instillation intraperitoneally and at port site. Subjects and Methods: Our study is a randomized controlled study of 90 cases of symptomatic cholelithiasis admitted and operated upon during the period of 24 months in the department of general surgery of our institute. The patients were randomly divided into 3 groups, Group A received intraperitoneal instillation of 20 ml of 0.5% Bupivacaine on gall bladder fossa and subdiaphragmatic region. Group B received 10 ml of 0.5%. bupivacaine on gall bladder fossa subdiaphragmatic and 10ml at the port site. Group C was the Control group who has not received any local analgesia. Postoperative pain and shoulder tip pain were then compared using Visual Analogue Scale (VAS) and Verbal Rating Scale (VRS). Results : At 2 and 4 hours pain score significantly more in Group C compared to Group B and A. After 8 hours there was no difference in pain score in all 3 groups. Time to receive first analgesia is significantly longer in group B compared to other groups. No difference in the shoulder pain in any of the groups. Conclusion: The instillation of Bupivacaine at the port site and intra-peritoneally (at the gallbladder fossa and sub-diaphragmatically), significantly decreases the pain in initial post-operative period in laparoscopic cholecystectomy.